The Potential of Cassava Leaves as a Component of Complete Ruminant Feed Formulated with Odot Grass - Pinem, Alda Maysa; Ardiansah, Yudha; Nafisah, Nyimas Rizka; Azzahra, Alifa; Hartutik; Asri Nurul, Huda (CV. Komunitas Dunia Peternakan, 2025)
This study aimed to evaluate the effect of substituting cassava leaves (Manihot esculenta Crantz) into a complete feed based on odot grass (Pennisetum purpureum cv. Mott) on in vitro rumen fermentation characteristics, including gas production, dry matter degradation (DMD), organic matter degradation (OMD), ammonia (NH₃) concentration, and microbial protein synthesis. A laboratory experiment was conducted using a Completely Randomized Design (CRD) consisting of five dietary treatments (0%, 5%, 10%, 15%, and 20% cassava leaf inclusion) with four replications each. The feed samples were incubated for 48 hours using rumen fluid collected from slaughtered Limousin cattle, selected purposively from the Ruminant Abattoir in Malang City based on consistent diet and health status to minimize variability. Feed ingredients were sun-dried, ground, and mixed into complete feed formulations using standardized proportions. In vitro gas production was measured using a gas-tight syringe technique, while DMD and OMD were calculated by weighing residues after fermentation. NH₃ concentrations were analyzed using the Conway microdiffusion method, and microbial protein synthesis was estimated based on the weight of microbial biomass derived from fermentation residues. All variables were statistically analyzed using ANOVA followed by Duncan’s Multiple Range Test at a 5% significance level. The results showed that a 20% substitution of cassava leaves significantly (P<0.01) improved the gas production rate, DMD, OMD, NH₃ concentration, and microbial protein synthesis, while decreasing gas production potential. These findings demonstrate the potential of cassava leaves as a sustainable protein-rich ingredient in ruminant complete feed formulations.